Conversion of Solid Waste into Wealth within Bauchi Metropolis (Waste Paper Recycling) - Muhammad, Salisu Umar; Anas Babangida; Suleman Ahmed Wan (Balai Publikasi Indonesia, 2025)
Waste paper recycling is a process by which waste paper, agricultural residues, waste cotton, old rugs, tailor cuttings, waste jute, hosiery cuttings, are processed together with some chemicals like caustic soda, dry staffs, resin, etc. The residential area in Bauchi metropolis generate an average volume of waste of about 0.003m3/person /day for high density areas, 0.005m3 /person /day for high density areas. This bring about the needs to recycle the waste in order to protect the environment. The study was conducted based on linker scale questionnaire primary and secondary data collection. And using some selected tertiary institutions such as, Abubakar Tafawa Balewa University, Federal poly technic, Abubakar Tatari Ali Poly technic, College of Agriculture Bauchi and Bauchi state secretariat were used as sampling size. The study also revealed that the average paper waste generated weekly is 10kg. Also the cost of the finance when it starts to operate at full capacity within 3 years, and the project’s initial investment will be fully recovered within 8 years. And the total amount of waste paper generated in the year 2016 within the study area was 68 tones. The recycled waste obtained from the solid waste will be used to generate new valuable products, sanitize the environment and also lead to job creation for the teaming unemployed youth.